Аналіз систем моніторинга в системах WDM - Лаптев, П. О. (ХНУРЕ, 2020)
The given work is devoted developments in the field of fiber networks and in monitoring systems. One of the most important tasks in transport networks, this is maintaining the characteristics of fiber and other optical elements at the proper level. Monitoring systems allow continuous monitoring. Different algorithms can describe monitoring. Monitoring has different modes. The presented algorithm is associated with the observation mode. The proposed algorithm helps to understand the principle of operation of this mode. This mode already exists in one of the specialized programs.